2018
DOI: 10.1108/acmm-05-2018-1941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat on microstructural, mechanical and electrochemical evaluation of tungsten inert gas welding of low-nickel ASS

Abstract: Purpose The purpose of the study is to evaluate Cr-Mn ASS weld using different heat inputs for its microstructure, mechanical properties and electrochemical behavior. The microstructural examination used optical and scanning electron microscopy. It was observed that ferrite content decreases with increasing heat input. The length of dendrites, inter-dendritic space and volume of lathy ferrite increase with increasing heat input. The increasing heat input caused grain coarsening near the fusion boundary and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(36 reference statements)
1
8
1
Order By: Relevance
“…Therefore, the LHI weldment exhibits better corrosion resistance than HHI weldment. These results are consistent with the results obtained by EIS Nyquist and Bode plots and also are consistent with the findings of other authors [25,26].…”
Section: Potentiodynamic Polarization Testsupporting
confidence: 94%
See 4 more Smart Citations
“…Therefore, the LHI weldment exhibits better corrosion resistance than HHI weldment. These results are consistent with the results obtained by EIS Nyquist and Bode plots and also are consistent with the findings of other authors [25,26].…”
Section: Potentiodynamic Polarization Testsupporting
confidence: 94%
“…It can be observed that the dendritic length and interdendritic arm spacing increase with increase in heat input. The faster cooling rate in the LHI process might help in suppressing the dendritic size and cell spacing formation as reported by authors [25,26]. Therefore, the increase in dendritic length and interdendritic arm spacing in the HHI process can be ascribed to a slower cooling rate.…”
Section: Microstructural Evolutionmentioning
confidence: 64%
See 3 more Smart Citations